Fully reflective photon sieve. (February 2018) - Sun, Wenbo; Hu, Yongxiang; MacDonnell, David G.; Kim, Hyun Jung; Weimer, Carl; Baize, Rosemary R.
Highlights: A concept of reflective photon sieve is developed in this work. It is based on a transparent membrane backed by a mirror. Light incident on this optical device is reflected and focused on its focal point. This component can perform the joint function of lenses and gratings/etalons. Abstract: Photon sieves (PS) have many applications and various designs in focusing light. However, a traditional PS only has a light transmissivity up to ∼25% and a focusing efficiency up to ∼7%, which hinder the application of them in many fields, especially for satellite remote sensing. To overcome these inherent drawbacks of traditional PSs, a concept of reflective photon sieve is developed in this work. This reflective photon sieve is based on a transparent membrane backed by a mirror. The transparent membrane is optimally a fully transparent material sheet with given refractive index and designed geometric thickness which has an optical thickness of a quarter incident wavelength (i.e. an anti-reflective coating). The PS-patterned pinholes are made on the transparent membrane. The design makes the light reflected from pinholes and that from zones of membrane material have 180° phase difference. Thus, light incident on this optical device is reflected and focused on its focal point. This device can have a reflectivity of ∼100% and a focusing efficiency of ∼50% based on numerical simulation. This device functions similar to a concave focusing mirror but can preserve the phase feature of light (such as that for the light with orbital angular momentum). It also has excellent wavelength-dependent property, which can exclude most of the undesired light from the focal point. A thin sheet of this component can perform the joint function of lenses and gratings/etalons in the optical path of a remote sensing system, thus is suitable for controling/filtering light in compact instruments such as satellite sensors. This concept is validated by the finite-difference time domain (FDTD) modeling and a lab prototype in this study.